EFFECTIVENESS OF LAW NUMBER 41 THE YEAR 1999 IN THE CASE OF ILLEGAL LOGGING IN MALUKU PROVINCE - La Ode Angga La Ode Angga; Barzah Latupono; Muchtar A Hamid Labetubun; Sabri Fataruba (Cepalo, 2019)
Ambon City and West Seram Regency (SBB) or SBB Regency, especially in Kairatu sub-district, the condition of the forest was once beautiful and green, but now, that condition has changed, the beautiful and green has changed into a stretch of land and barren grasslands. The above conditions will affect the water cycle by decreasing water discharge as a source of life for the community. The problems that will be examined in this study are is why the legal provisions in the forestry sector are not effective in communities living around State forest areas in the Maluku Province? What factors are lead the community members who live around the State forest to be obliged to implement the legal provisions in the forestry sector in the State forest area in the Maluku Province? This research was conducted by an empirical juridical approach which is descriptive qualitative analysis. The research seeks to illustrate what is happening in the communities living around the State forest in Maluku Province. The result of this research is Law No. 41 of 1999 on Forestry in Maluku province, in the city of Ambon City and West Seram District (SBB). Factors that cause residents living in the forest in the region of Maluku, the illegal logging and the second factor is the low level of awareness of the people living around the State forest area in the location of this study.